Effects of phenolic acid metabolites formed after chlorogenic acid consumption on retinal degeneration in vivo - Jang, Holim; Choi, Yongsoo; Ahn, Hong Ryul; Jung, Sang Hoon; Lee, Chang Yong (WILEY, 2015)
Scope: Although ingestion of coffee and its constituent chlorogenic acid (CGA) protects the retina from oxidative stress, the bioaccessibility and bioavailability of coffee metabolites are not well understood. The aim of this study was to determine which coffee metabolites reach the retina and protect against retinal degeneration. Methods and results: UPLC-MS/MS was used to detect CGA and coffee metabolites in the rat eye. The methyl thiazolyl tetrazolium assay and double staining with Hoechst and propidium iodide showed that CGA, caffeic acid (CA), and dihydrocaffeic acid (DHCA) protect retinal ganglion cells from hypoxia-induced damage. Western blots showed that treatment with coffee metabolites up-regulated anti-apoptotic proteins such as Bcl-2 and Bcl-X-L and down-regulated pro-apoptotic proteins such as Bad, PARP, and cleaved caspase 3. Adult ICR mice were subjected to optic nerve crush-induced retinal ganglion cell death with intravitreal pre-treatment with coffee metabolites 1 day before and 1 h after the procedure. Retrograde Fluorogold (TM) labeling showed severe retinal ganglion cell loss after optic nerve crushing, and coffee metabolites significantly reduced damage to retinal ganglion cells. Conclusion: CGA and coffee metabolites, especially, CA, and DHCA, reach the eye, where they can significantly reduce apoptosis induced by hypoxia and optic nerve crush stress, and thus prevent retinal degeneration.